Fenomena Akuntabilitas Terhadap Pendanaan Lembaga Swadaya Masyarakat - Bramasta Noviantoro; Paskah Ika Nugroho (AFRE (Accounting and Financial Review), 2019)
Public confidence in NGOs has decreased in a number of countries, reported from the trust barometer data in 2018 17 of 28 countries experienced a decline in the level of trust in NGOs. One reason for the reduced level of public confidence in NGOs which has led to the inhibition of NGO funding is accountability. The aim of this research is to investigate the funding and the accountability phenomenon of NGOs that carry out community development in the East Nusa Tenggara region. This research method uses interview techniques with interviewees who are directly positioned as accountant advisors on the NTA. The results of this study provide evidence that the level of accountability influences the level of trust of funders in providing their funds for future NGO programs. DOI: https://doi.org/10.26905/afr.v2i2.3671